Nonverbal content analysis on food vlogger Instagram account @kulinersimamank - Muhammad Azis Faturrohman; Faradila Imeliyanti; Khaerudin Imawan (Green Publisher Indonesia, 2025)
Content is the main key that needs to be considered in social media because the quality of the content will determine whether or not the message is conveyed. One aspect that is often overlooked in food vlogging content analysis is nonverbal communication messages. The purpose of this study is to explore and analyze nonverbal elements in food vloggers' content, as well as their impact on audience engagement. The research method uses qualitative with data triangulation techniques. This research uses John Greene's action assembly theory. The results of this study @kulinersimamank account successfully applies John Greene's message production theory by presenting entertaining content, as well as building strong engagement with the audience. Through a deep understanding of culinary and the use of nonverbal communication, this account creates effective interactions and builds an emotional connection with the audience.